Students’ Perceptions on the Use of Google Classroom in Writing Activities: A Case Study - Adeliya Lestari; Manalulaili Manalulaili; Winny Agustria Riznanda (Edukasi, 2021)
Google classroom is an application for online learning and teaching. The objective of this study was to find out the students’ perceptions on the use of google classroom in writing activities at SMAN 3 Lubuklinggau. The qualitative research method with a case study research design was used in this study. The participants of this study were six students who were obtained by using a maximum variation sampling based on teacher’s recommendation. The study used interview and thematic analysis was selected as analyzing the data in developing categories and sub-categories of the data. The findings showed that there were positive and negative perceptions on the use of Google Classroom in writing activities. They were (1) being easy to acces, (2) saving time, (3) getting feedback, (4) being easy to post writing assignments, (5) having lack of interaction, and (6) increasing problem in writing. The results showed that google classroom used in online learning had advantages and disadvantages for students in learning writing.